Medical and Surgical Management of Congenital Laryngomalacia: A Retrospective Case‐Control Study. (2nd September 2014) - Faria, John; Behar, Philomena
Abstract : Objectives: Compare the growth of infants with moderate to severe laryngomalacia who underwent supraglottoplasty to the growth of those treated with medical therapy alone. Methods: Retrospective case‐control chart review of patients treated between 2008 and 2013 in a tertiary care pediatric otolaryngology practice. 51 infants newly diagnosed with moderate to severe congenital laryngomalacia were included. A total of 17 infants underwent supraglottoplasty and 34 matched controls had medical management, which included acid suppression therapy, speech and swallowing therapy, and/or high‐calorie formula. The primary outcome measure was weight percentile recorded at the second clinic visit and at the last available follow‐up. The secondary outcomes were the need for tracheostomy or gastrostromy, development or persistence of failure to thrive, surgical complications, and new onset developmental delay. The management strategy was considered a success if none of the secondary outcomes occurred. Results: There was no difference in the mean weight percentile between the surgical and nonsurgical groups at the time of last follow‐up ( P =. 89). Twenty‐nine (85%) patients in the medical management group and 12 (71%) in the surgical group were managed successfully. There were no statistically significant differences in the success rate between groups ( P =. 27). Conclusions: Medical management and close observation of infants with moderate to severe congenital laryngomalacia may be a viable alternative to supraglottoplasty.